2018
DOI: 10.1021/acs.joc.8b00640
|View full text |Cite
|
Sign up to set email alerts
|

Desymmetrization of Cyclopropenes via the Potassium-Templated Diastereoselective 7-exo-trig Cycloaddition of Tethered Amino Alcohols toward Enantiopure Cyclopropane-Fused Oxazepanones with Antimycobacterial Activity

Abstract: A strain-release-driven, cation-templated intramolecular nucleophilic addition of tethered alkoxides to prochiral cyclopropenes is described. Employment of chiral β- and γ-amino alkoxides allowed for highly diastereoselective assembly of a small series of enantiopure cyclopropane-fused oxazepanones. It was shown that the chiral center at C-4 plays a crucial role in controlling desymmetrization of the cyclopropenyl moiety, instigated by a profound potassium-templated effect. The preliminary biological activitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…We have recently reported on the key role of potassium cations in the chelation-controlled cyclization of cyclopropenes 4 linked to nucleophilic alkoxide moieties. [27][28][29] This innovative approach allows for a highly efficient and diastereoselective assembly of cyclic ethers 5 with ring sizes 7 to 10 (Scheme 1). [27][28][29] These bicyclic structures produced new, highly selective anti- mycobacterial agents.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We have recently reported on the key role of potassium cations in the chelation-controlled cyclization of cyclopropenes 4 linked to nucleophilic alkoxide moieties. [27][28][29] This innovative approach allows for a highly efficient and diastereoselective assembly of cyclic ethers 5 with ring sizes 7 to 10 (Scheme 1). [27][28][29] These bicyclic structures produced new, highly selective anti- mycobacterial agents.…”
Section: Resultsmentioning
confidence: 99%
“…[27][28][29] This innovative approach allows for a highly efficient and diastereoselective assembly of cyclic ethers 5 with ring sizes 7 to 10 (Scheme 1). [27][28][29] These bicyclic structures produced new, highly selective anti- mycobacterial agents. 29 Closely related diazepinones and diazecanones 7 demonstrated antitumor activity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our research group has extensive experience in controlling the chemo- and stereoselective assembly of medium-sized rings by employing the metal-templated addition of oxygen- , or nitrogen-based nucleophiles to functionalized cyclopropenes. We showed that this approach allowed for the highly efficient cyclization of 7- to 10-membered rings. We envisioned that a cyclopropene unit could also serve as a practical rigidified linchpin for a “click–click–cyclize” approach , to prepare medium-sized lactams via RCM. Herein we now disclose on the design and realization of this diversity-oriented synthetic strategy.…”
mentioning
confidence: 99%